Definitive therapy for a rare cause of recurrent ascites. Issue 3 (19th April 2012) - Naghibi, Mani; Ward, Robert; Shutt, James
Abstract : Extrahepatic arterioportal fistulas are a rare cause of portal hypertension in infants and adults. Most cases of arterioportal fistulas in adults are due to trauma, liver biopsy, surgery or tumours. The authors present a case of arterioportal fistula diagnosed in adult life without any of the above aetiologies. The patient became acutely symptomatic with diarrhoea and ascites at the age of 66 years and was successfully treated with a single endovascular embolisation procedure after failed medical therapy.